2020
DOI: 10.1038/s41467-020-19310-x
|View full text |Cite
|
Sign up to set email alerts
|

All-dielectric magnetic metasurface for advanced light control in dual polarizations combined with high-Q resonances

Abstract: Nanostructured magnetic materials provide an efficient tool for light manipulation on sub-nanosecond and sub-micron scales, and allow for the observation of the novel effects which are fundamentally impossible in smooth films. For many cases of practical importance, it is vital to observe the magneto-optical intensity modulation in a dual-polarization regime. However, the nanostructures reported on up to date usually utilize a transverse Kerr effect and thus provide light modulation only for p-polarized light.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 54 publications
1
57
1
Order By: Relevance
“…This mode itself is completely insensitive to component of the magnetic field [ 32 ]. However, if a magnetic field in polar configuration ( ) is applied, the eigen polarization of the mode changes [ 36 , 37 ] and it acquires TM-components that were absent in the nonmagnetic case. In its turn, the emerged TM-components are sensitive to the switching of the direction of the component of the external magnetic field.…”
Section: Resultsmentioning
confidence: 99%
“…This mode itself is completely insensitive to component of the magnetic field [ 32 ]. However, if a magnetic field in polar configuration ( ) is applied, the eigen polarization of the mode changes [ 36 , 37 ] and it acquires TM-components that were absent in the nonmagnetic case. In its turn, the emerged TM-components are sensitive to the switching of the direction of the component of the external magnetic field.…”
Section: Resultsmentioning
confidence: 99%
“…[73] The high FoM and the single-layer growth process make Ce and especially Bi-substituted TbIG attractive materials for integrated nonreciprocal photonic devices or for other applications requiring MO materials such as magnetophotonic crystals or other nonreciprocal MO metamaterials. [74,75] [12] of 99.999% pure Tb 2 O 3 , CeO 2 , Bi 2 O 3 , and Fe 2 O 3 powders. The films were grown at a repetition rate of 10 Hz and laser fluence of 1.5 and 2.5 J cm −2 .…”
Section: Discussionmentioning
confidence: 99%
“…9. Ignatyeva et al [73] observed the intensity modulation of transparent all-dielectric MO metasurfaces composed of 2D nanopillar array on an ultrathin irongarnet slab in a dual-polarization regime, which was very promising for sensing, vector magnetometer, and light modulation applications.…”
Section: Magnetoplasmonic and Magneto-optical Metasurfacesmentioning
confidence: 99%